Correlation of Total Body Fat and Physical Fitness Index in Medical Students of Universitas Islam Indonesia - Firdaus, Lidya Sabilla; Pramaningtyas, Miranti Dewi; Nugraha, Zainuri Sabta (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2021)
The World Health Organization suggests that total body fat is one of the main risk factors for metabolic syndrome which is the most significant cause of morbidity and mortality in the world. The excessive fat mass harms the function of the heart, lowers the oxygen uptake by working muscles. Excess of body fat may decrease physical fitness. This research aims to know the correlation of total body fat with physical fitness index in medical students of Universitas Islam Indonesia. This research used a cross-sectional study design. The research subjects consisted of 45 male medical students of Universitas Islam of Indonesia under 25 years old. Total body fat of its subject is measured by Bioelectrical impedance analysis method (Karada scan), while physical fitness index is measured by the Harvard Step Test. This study is tested by Spearman correlation. Mean of TBF (%) value was 23.68 Â± 6.29. Mean of physical fitness index levels was 60.05 Â± 31.27. Spearman correlation test has a result r = -0.314 with a significance of p = 0.038 (p<0.05), that means total body fat and physical fitness index has a significant negative correlation. There was a significant negative correlation between total body fat and physical fitness index